A New Approach to Health Literacy: Working with Spanish Speaking Community Health Workers. Issue 1 (2nd January 2017) - El-Khayat, Yamila M.
ABSTRACT: This case study describes the integration of pop culture, music, and scenarios into a consumer health curriculum for community health workers (CHW)/Promotoras De Salud of Hispanic/Latino decent. The class goal is to ensure that participants learn about reliable health resources and how to use them when reaching out to their clientele. This interactive approach to teaching consumer health information was something that evolved after teaching this topic for many years and finding the need to reach the CHW population and enhance their learning experience of health information.